Clinical Evaluation and Operational Integration of Autorefractors in Optometry Practice: Accuracy, Workflow Efficiency, and Patient-Centered Visual Outcomes - Alanazi, Sulaiman Gayadh; Shatha Hamad Almdhour; Ibrahim Abdullah Aldowaish; Waad Alqahtani; Khaled Khalaf Alanazi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Manual refraction has long been the gold standard for determining refractive error, but its reliance on operator skill and patient cooperation introduces variability and inefficiency. Autorefractors offer an objective, rapid alternative, leveraging optical principles and computational algorithms to enhance workflow and accuracy in optometry practice. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This study evaluates the clinical accuracy, operational efficiency, and patient-centered outcomes associated with autorefractor integration in routine eye-care workflows. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive review of historical development, optical principles (Scheiner’s and optometer), device engineering, and clinical deployment was conducted. Key parameters analyzed include measurement reliability, workflow impact, and limitations across diverse patient populations and ocular conditions. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Modern autorefractors demonstrate high repeatability and speed, reducing chair time and supporting high-volume clinics. They provide reliable baseline estimates for myopia, hypermetropia, and astigmatism, though accuracy may decline in cases of accommodation fluctuation, irregular corneas, or media opacity. Integration with electronic systems and delegation to trained staff improves throughput and team efficiency. However, artifacts such as proximal accommodation and fixation instability remain significant pitfalls, necessitating clinical oversight and subjective refinement. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Autorefractors are indispensable tools in contemporary optometry, offering objective, standardized measurements that enhance workflow and patient experience. While not a substitute for clinical judgment, their strategic use improves efficiency and supports patient-centered care when combined with subjective techniques.